Riflessioni su diritto e religione a margine del Martin Luther King Day (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. Advocate of the social Gospel: Martin Luther King e il percorso americano di riforma della legislazione sui diritti civili - 3. Post-colonialismo e terzomondismo: Martin Luther King e i percorsi di liberazione su scala globale - 4. Martin Luther King e Gandhi, Cesar Chavez e Sayyed Qutb - 5. Conclusioni: diritti religiosi, giustizia globale e stato di diritto.Remarks about Law & Religion for the Martin Luther King DayABSTRACT: April 4, 2018 commemorates the fiftieth anniversary of the death of Martin Luther King jr., in Memphis-Tennessee. The importance of Martin Luther King’s personality goes far beyond the borders of United States and spreads on the global scale. The present paper concerns the universality and the present impact of Martin Luther King’s legacy, considering also the European context. The paper analyses in brief the history of Martin Luther King, taking into account both his activism in the US and his international criticism against global issues such as post-colonialism and third-worldism; a second part is dedicated to the so called religious “global left” of the 50s and 70s. Conclusions show how and why the global religions have still to be considered a critical background for the rule of law, its inequalities and its injustices.
Keywords: Varie